2016
DOI: 10.1007/s12630-016-0741-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison between intravenous and perineural dexamethasone for ultrasound-guided axillary block

Abstract: Background This randomized double-blinded trial compared the effect of intravenous and perineural dexamethasone (8 mg) on the duration of motor block for ultrasound (US)-guided axillary brachial plexus block (AXB). Methods Patients undergoing upper limb surgery with US-guided AXB were randomly allocated to receive preservative-free dexamethasone (8 mg) via intravenous (n = 75) or perineural (n = 75) administration. The local anesthetic agent, 1% lidocaine -0.25% bupivacaine (30 mL) with epinephrine 5 lgÁmL -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 25 publications
0
47
2
Order By: Relevance
“…In the absence of placebo group, the prolongation obtained with intravenous dexamethasone could not be precisely determined. A duration of analgesia of 17.1 hours was reported with intravenous dexamethasone, lower than the one we observed in our study 4. This difference may be explained by: (1) the local anesthetic used (30 mL of a mixture of 1.5% lidocaine, 0.25% bupivacaine, and 5 µg/mL epinephrine vs 0.5 mL/kg 0.475% ropivacaine in our study), (2) the outcome criteria (duration of motor block vs time before analgesic intake), and (3) a different technique for APB (perivascular vs perineural injections).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In the absence of placebo group, the prolongation obtained with intravenous dexamethasone could not be precisely determined. A duration of analgesia of 17.1 hours was reported with intravenous dexamethasone, lower than the one we observed in our study 4. This difference may be explained by: (1) the local anesthetic used (30 mL of a mixture of 1.5% lidocaine, 0.25% bupivacaine, and 5 µg/mL epinephrine vs 0.5 mL/kg 0.475% ropivacaine in our study), (2) the outcome criteria (duration of motor block vs time before analgesic intake), and (3) a different technique for APB (perivascular vs perineural injections).…”
Section: Discussioncontrasting
confidence: 90%
“…In APB block, a longer duration of analgesia was reported when dexamethasone was administered perineurally compared with intravenous route 4. Results of recently published systematic reviews and meta-analysis of randomized controlled trials comparing perineural and intravenous dexamethasone in various type of RA are controversial, showing either greater or equivalent efficacy of perineural versus intravenous route 1–3 16 17.…”
Section: Discussionmentioning
confidence: 99%
“…scores of 14 points at 30 minutes (89%-95%) have always slightly underestimated the true incidence of surgical anesthesia (95%-99%). 4,12,13 However, from an ethical standpoint and for patient care, it is preferable for surrogate markers to err on the side of caution rather than to overestimate the true incidence of surgical anesthesia. Thus, in clinical practice, we expect the MEV90 reported in this study to provide a very reliable costoclavicular ICB.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite the role of IV dexamethasone being well established, the benefit of placing dexamethasone in a more targeted (perineural) fashion is unclear, and recent randomized controlled trials (RCTs) have revealed conflicting results as to whether such perineural dexamethasone is superior to its IV counterpart for prolonging analgesic duration. 5,6 This question is important: on one hand, such targeted administration of dexamethasone may in theory improve its ability as an adjuvant; on the other hand, animal studies show that certain perineural adjuvants are toxic and dexamethasone's usage for perineural administration is currently off-label. 7,8 Given this clinical equipoise and conflicting results from RCTs, 5,6 we designed and conducted a systematic review and meta-analysis of RCTs to delineate the benefits, if any, of perineural administration of dexamethasone compared to its IV counterpart.…”
mentioning
confidence: 99%
“…5,6 This question is important: on one hand, such targeted administration of dexamethasone may in theory improve its ability as an adjuvant; on the other hand, animal studies show that certain perineural adjuvants are toxic and dexamethasone's usage for perineural administration is currently off-label. 7,8 Given this clinical equipoise and conflicting results from RCTs, 5,6 we designed and conducted a systematic review and meta-analysis of RCTs to delineate the benefits, if any, of perineural administration of dexamethasone compared to its IV counterpart. In particular, we were interested if perineural administration (compared to IV) prolonged the duration of analgesia for single-shot nerve blocks of the upper or lower limb and if the usage of perineural dexamethasone led to any acute or permanent postblock sequelae, such as prolonged paresthesias, numbness, or weakness.…”
mentioning
confidence: 99%